Analisis Faktor-Faktor Yang Mempengaruhi Minat Nasabah Memilih Tabungan Produk Wadiah Pada Bank Dki Syariah KCP Matraman - Muhammad Faizin Akbar; Hartini Salama; Agus Salim (DPW FORSILADI SULSEL, 2025)
This research aims to analyze the factors that influence customer interest in choosing Wadiah savings products at Bank DKI Syariah KCP Matraman. The research method used is a qualitative approach by distributing questionnaires to customers who have Wadiah savings. The factors studied include understanding sharia principles, level of trust, ease of access to services, and promotions carried out by banks. The data obtained was analyzed using multiple linear regression to identify the most dominant factors influencing customer decisions. The research results show that the level of trust and understanding of sharia principles has a significant influence on customer interest, while ease of service access and promotions have a lower influence. These findings provide recommendations to Bank DKI Syariah to further improve education related to sharia principles and strengthen customer trust as the main strategy in increasing interest in Wadiah products.